Assessment of turbulence models for the boundary layer transition flow simulation around a hydrofoil. (1st December 2020) - Ye, Changliang; Wang, Fujun; Wang, Chaoyue; van Esch, Bart P.M.
Abstract: Boundary layer transition is a typical phenomenon in flows around hydrofoils and has a large influence on the hydrodynamic characteristics such as lift & drag, and vortex shedding. The purpose of this paper is to assess the predictive capability of different turbulence models in computational fluid dynamics (CFD) on boundary layer transition along a hydrofoil. Two typical sub-grid scale (SGS) stress models (LES WALE and LES Smagorinsky), as well as DDES γ-Re θt, DDES, SSTCC γ-Re θt, SST γ-Re θt, and SST k − ω are selected. The boundary layer and wake flow calculated by different models are analyzed in detail and compared with the experimental data. The results show that large eddy simulation is more accurate than other models in terms of boundary layer velocity distribution, vortex shedding and wake structure prediction at the same grid conditions. The transition model considering curvature correction influences the predictive capability in the near-wall region compared with SST γ-Re θt . The flow fields calculated by different curvature correction coefficients are quite different. In this paper, the prediction in the front of the transition end point (0.85 L ) has achieved good results as scaling coefficient is equal to 75 or 100. The transition model considering curvature modification improves the prediction of boundary layer transition by decreasing the turbulence intensity and increasing the pressure gradient of the aft part of the curvature hydrofoil leading. It is found that the LES model is the first choice in the case of enough computing resources. However, for engineering problems, it is highly efficient to adopt SSTCC γ-Re θt model by adjusting the curvature correction coefficient. Highlights: Comparisons of boundary layer transition flow around a hydrofoil predicted by turbulence models are carried out. Influence of the curvature coefficient of the SSTCC γ-Re θt model on the boundary layer prediction is found. Reasons of transition model prediction changed by adjusting the curvature coefficient are discussed.